Role of Early Assesment of Diuresis and Natriuresis in Detecting In-Hospital Diuretic Resistance in Acute Heart Failure - García-Magallón, Belén; Cobo-Marcos, Marta; Martiarena, Aitor Dávila; Hernández, Esther Montero; Martín Jiménez, Maria Luisa; García, Aránzazu Martín; De Castro Campos, Daniel; Martín, Paula Vela; Terciado, Fernando Hernández; González, Ramón Garrido; Matutano Muñoz, Andrea; Escribano García, Daniel; et al. (Frontiers in Physiology, 2022)
Background and Purpose: European Guidelines recommend early evaluation of diuresis and natriuresis after the first administration of diuretic to identify patients with insufficient diuretic response during acute heart failure. The aim of this work is to evaluate the prevalence and characteristics of patients with insufficient diuretic response according to this new algorithm. Methods: Prospective observational single centre study of consecutive patients with acute HF and congestive signs. Clinical evaluation, echocardiography and blood tests were performed. Diuretic naïve patients received 40 mg of intravenous furosemide. Patients on an oupatient diuretic regimen received 2 times the ambulatory dose. The diuresis volume was assessed 6 hours after the first loop diuretic administration, and a spot urinary sample was taken after 2 hours. Insufficient diuretic response was defined as natriuresis < 70 mEq/L or diuresis volume < 600 ml. Results: From January 2020 to December 2021, 73 patients were included (59% males, median age 76 years). Of these, 21 patients (28.8%) had an insufficient diuretic response. Diuresis volume was < 600 ml in 13 patients (18.1%), and 12 patients (16.4%) had urinary sodium < 70 mEq/L. These patients had lower systolic blood pressure, worse glomerular filtration rate, and higher aldosterone levels. Ambulatory furosemide dose was also higher. These patients required more frequently thiazides and inotropes during admission. Conclusions: The diagnostic algorithm based on diuresis and natriuresis was able to detect up to 29% of patients with insufficient diuretic response, who showed some characteristics of more advanced disease.